Influence of different treatment procedures on the temporomandibular joint after mandibular setback in skeletal class III - A retrospective study. Issue 9 (September 2022) - Ohba, Seigo; Tominaga, Junya; Shido, Rena; Koga, Takamitsu; Yamamoto, Hideyuki; Zaiima, Hirotaka; Yoshida, Noriaki; Asahina, Izumi
Abstract: The aim of this study was to clarify the effects of three different orthognathic surgical procedures on the temporomandibular joint after mandibular setback. Conventional sagittal split ramus osteotomy (SSRO) with segmental fixation (conv-SSRO), intraoral vertical ramus osteotomy (IVRO), or SSRO without fixation followed by the physiological positioning strategy (nonfix-SSRO) was performed for mandibular setback. Temporomandibular joint disorder (TMD) symptoms were clinically assessed, and the condylar head angle was measured. In total, 129 patients participated. Preoperative TMD and treatment procedure were related to postoperative TMD. A menton deviation of 3.43 mm was the cutoff for the risk of postoperative TMD. The incidence rate of postoperative TMD in the conv-SSRO group was higher than that in the IVRO ( p = 0.0197) and nonfix-SSRO ( p = 0.0001) groups in asymmetric cases. There was no significant postoperative change in the temporomandibular joint space in each group. In symmetric and asymmetric cases, the condylar head was rotated inwards by 5.82 ± 4.75° ( p < 0.0001) and 5.44 ± 3.10° ( p < 0.0001), respectively, in the conv-SSRO group, and outwards by −7.98 ± 5.05° ( p < 0.0001) and −8.32 ± 6.38° ( p < 0.0001), respectively, in the IVRO group, but it was almost stable in the nonfix-SSRO group. Within the limitations of the study it seems that nonfix-SSRO should be preferred over conv-SSRO and IVRO whenever appropriate.